(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper continued a detail review of heat pipe and thermoelectric generator application in industrial, automobile and solar waste heat recovery. Each day new greenhouse gasemission further accelerates global warming. The exhaust heat recovery system by usingheat pipe and TEGsis topotentially reduce the greenhouse gases emission. The use of two specific technologies heat pipe and TEGs make passivesolid state system design. Heat pipe used in system consents more flexible design as TEG location not inadequate to exhaust pipe surface. The conversion efficiency of thermoelectric generator is function of temperature difference Heat source and heat sink temperature. The thermal performance of thermoelectric generator will be improved or enhanced by using heat pipe as a heat source in thermoelectric generator. Heat pipes do have limitations such as maximum rates of heat transfer and temperature limits. TEGs do have limitations such as low temperature limits and relatively low efficiency. When used in conjunction, these technologies have the potential to create a completely solid state and passive waste heat recovery system.